(untitled) (Praxis Educativa, 2026)
The purpose of this article is to analyze the place of childhood in popular education. To this end, we offer a brief reconstruction of both the history of popular education and the education (also popular) of popular children linked to experiences of political participation in social movements. Despite the fact that since the end of the 1970s significant political-pedagogical experiences have been unfolding (and are increasingly recognized) with children who have focused on the promotion of their protagonism, and which are recognized in the tradition of popular education, these experiences do not seem to have taken place within the history of popular education. Hence, from a non adultcentric perspective, it is hypothesized that both the history and the theory of popular education have been —predominantly— the history and theory of an emancipatory pedagogical-political conception conceived and directed to the adult world.